THE INFLUENCE OF LOCATION, SERVICE QUALITY AND PRICE PERCEPTION ON WORKSHOP CUSTOMER SATISFACTION (Study on SBR AC/Audio Kendal Workshop) - Adi Rahman Prasetya; Rokh Eddy Prabowo (SEAN Institute, 2023)
The purpose of this study was to analyze the effect of location, service quality, and price perceptions on customer satisfaction in Kendal's SBR AC/AUDIO workshop. The method used is a quantitative research method. The population in this study were all consumers who had Kendal AC/AUDIO repair services. The number of samples is 72 respondents determined by accidental sampling technique. The data analyzed were primary data collected by questionnaire and processed using SPSS version 22. Based on data processing, the following results were obtained: The instrument was declared valid and reliable. The results of the test for the coefficient of determination (R2) show that the ability of the independent variables to explain the dependent variable is 0.849 percent. The results of the t test show that the location variable has a significant effect on customer satisfaction, service quality has no significant effect on customer satisfaction, and price perceptions have a significant effect on customer satisfaction. The results of the regression coefficients of all independent variables were positive. Thus the results of the study indicate that location and price perceptions have a positive and significant effect on consumer satisfaction. And service quality is not significant to customer satisfaction.